Machining characteristics of oil palm wood treated with phenol formaldehyde resin using compress method - Chong, Yi Way (2011)
The objective of this study is to evaluate the machining characteristics of oil palm wood treated with phenol formaldehyde resin using compress method. This study is divided into three parts. The first and second parts of the machining study are based on ASTM 1666-87 standard and their surface roughnesses are assessed based on ISO 4288 standard. The first part of the study is on the planing characteristic of treated OPW, the second part of the research looked into the drilling and cross-cutting characteristic of treated OPW and finally the third part of research, examined the tool wear of tungsten carbide circular saw used to cut the treated OPW. The planing test showed that the treated OPW improved vastly from those of untreated OPW and on par with Rubberwood. In general, the planing of the treated OPW and the Rubberwood fell into the Grade I (very good), compared to Grade III (average) for untreated OPW. Surface roughness assessment from the test placed treated OPW close to those of Rubberwood range which are within 4 μm-12 μm, while the untreated OPW are averaged at 20 μm with some readings top the upper and lower limit of the profilometer. In the second part of the study, there were two tests - drilling and crosscutting. Drilling was done using four different Forstner bits to test the effects of diameter and rake angle of the bit toward the drilled holes. Smaller diameter (25 mm) and higher rake angle (30⁰) shows better result than those of bigger diameter (32 mm) and lower rake angle (20⁰). While for the crosscutting study, the quality of cut of treated OPW exceed Rubberwood and untreated OPW. In the final study, it was found that the treated OPW will cause more severe wear on the rake side of the saw tip followed by Rubberwood and untreated OPW. The clearance side of the saw tip had a more severe wear when cutting untreated OPW followed by treated OPW and Rubberwood. On average the tool wear rate of saw tip used to cut treated OPW is the highest followed by those used to cut untreated OPW and Rubberwood . In conclusion, the compress treatment, significantly improved the planing, drilling and cross-cutting characteristic of OPW. The treated OPW produced are comparable to Rubberwood if not better. Forstner bit with smaller diameters and higher rake angle gave a better result in sense of its bored quality. The treated OPW causes the cutting tool to wear but at a more gradual rate while the untreated OPW may cause chipping on the saw blade due to the splintering of the vascular bundles during cutting.